KESESUAIAN PENYIMPANAN VAKSIN COVID-19 DI INSTALASI FARMASI DI SALAH SATU DINAS KESEHATAN BENGKULU - Sari, Maritta; Sari, Nengke Puspita; Iskandar, Siska (Bengkulu Institute, 2024)
Stroke is the second cause of death and the third cause of disability in the world after heart disease and cancer in both developed and developing countries. The burden caused by stroke is mainly due to disability (public health problem) which also creates a highcost burden for both sufferers, families, society and the state. The impact of stroke in general is very diverse, such as impaired physical mobility, impaired verbal communication and even swallowing disorders, depending on the part of the brain that is damaged. If a stroke occurs in a part of the brain that plays an important role, such as the brain stem which regulates breathing, it can have serious impacts, one of which is swallowing disorders. Lesions that occur in the brain will result in impaired cognitive function such as impaired concentration and attention, which can interfere with the swallowing process, which can result in aspiration due to the entry of food and drink into the respiratory tract. Actions that can be taken to overcome swallowing difficulties in stroke patients are by performing Shaker Exercises. Shaker Exercise is a rehabilitation to strengthen weak muscles and overcome difficulty swallowing in the suprahyoid muscles of the neck. The community service method used is socialization and isometric and isotonic exercises carried out at the Harapan and Doa Hospital, Bengkulu City. After carrying out community service activities with mild stroke patients, it can reduce the problem of dysphagia in patients who suffer from stroke. It is hoped that the Shaker Exercise action will be applied as a nursing intervention while the patient is being treated in hospital.